USING ORAL PRESENTATION TO PROMOTE SPEAKING ENGLISH IN EFL/ESL CONTEXT: A Case Study at BELTEI International University, Phnom Penh, Cambodia - Dr. Loeung By; Bunthol Veng (JF Publisher, 2024)
Every university session includes an oral presentation to help students acquire confidence in their speaking skills. However, these are still challenging that university students and lecturers encounter while fostering speaking abilities in an EFL/ESL environment. This study looks at the obstacles that EFL/ESL lecturers experience when utilizing oral presentations to enhance speaking abilities, as well as techniques for increasing student confidence. The qualitative technique was utilized to collect interview data, and the quantitative approach was used to investigate the frequency and proportion of existing issues and practices by utilizing oral presentations to improve speaking abilities. The study discovered that student-related constraints are the most important impediments, with presentation-related concerns, teacher-related factors, language-related limits, and fluency challenges all contributing. To boost student confidence and increase oral presentation efficacy, the study suggests tactics such as establishing the presenting class, organizing the presentation, using visual aids, self-reflection, and offering positive feedback. While instructors who encouraged questions and held post-presentation Q&A sessions were found to be useful, there was more diversity in replies when lecturers wrote questions and provided more time or technological knowledge. Overall, the study underlines the significance of addressing both student and instructor characteristics in order to establish a supportive learning environment in EFL/ESL classrooms that promotes good oral communication.